Expert testimony on domestic violence a discourse analysis - Hamilton, Melissa, 1964- (Law and society (New York, N.Y.), 2009)
"Examines the impact of social science evidence on legal reasoning in domestic violence cases, analyzing the text and rhetoric from a body of appellate opinions in which expert witnesses provided social science-based testimony about domestic violence"--Provided by publisher.